Implementation of problem-based learning model in learning biology in the equality program - Ari Estiana, Nilna Tintan; Lestari, Gunarti Dwi; Yulianingsih, Wiwin; Masitha, Karina Dewi (Universitas Negeri Semarang, 2023)
Realizing the importance of learning, SKBN Surabaya tries to design a learning process that can meet the learning needs of students, especially the SKBN Surabaya Package C equivalency program, which consists of various ages. One learning model that provides opportunities for students to have the experience of discovering a concept and increasing their understanding and requires students to be more active in learning is the PBL (Problem-Based Learning) model. This study aimed to describe implementing the problem-based learning (PBL) model in learning biology in the package C equivalency program at SKBN Surabaya. This research used a qualitative descriptive approach. Data was collected by interviewing biology tutors and randomly selected students and observing during the learning process. The subjects used were all package C class X students, totaling 11 students. The data analysis model used included data collection, data condensation, data presentation, and conclusion/verification. The results showed that students were actively involved using the problem-based learning model during the learning process. In its application, the tutor has followed the five phases in the problem-based learning model: orienting students to the problem, organizing students, guiding individual and group investigations, developing and presenting results, and analyzing and evaluating the problem-solving process.